Asymptomatic pulmonary cryptococcosis presenting with mixed lesions of infiltrative and nodular shadow in an immunocompromised patient. Issue 12 (1st December 2022) - Ito, Takanori; Kanai, Osamu; Moriyoshi, Koki; Fujita, Kohei
Abstract : Pulmonary cryptococcosis (PC) is a rare fungal lung infection that usually occurs in immunocompromised hosts. We report a rare case of PC with asymptomatic and mixed lesions of infiltrative and nodular shadows. A woman in her 50s with a 7-year history of methotrexate treatment for rheumatoid arthritis (RA) presented with abnormal chest shadows on annual examination. Chest CT revealed two tiny nodules and two infiltrative shadows in the right lower lobe of the lung. We suspected lung cancer, cryptogenic organising pneumonia or RA-interstitial lung disease. However, transbronchial lung biopsy and positivity for serum cryptococcal antigen confirmed the diagnosis of PC. We initiated treatment with fluconazole, which drastically reduced the chest shadows without any adverse events. Since PC can present with several pulmonary shadows, it should be considered as a differential diagnosis of any pulmonary lesion.